Safety, immunogenicity of lyophilized purified vero cell cultured rabies vaccine administered in Zagreb and Essen regimen in post-exposure subjects: A post-marketing, parallel control clinical trial - Lei Zhang; Shichun Huang; Li Cai; Zhenggang Zhu; Jian Chen; Sha Lu; Zerong Zhu; Man Zhang; Yuan Fang; Quan Hu (Taylor & Francis Group, 2021)
To compare the safety and immunogenicity of lyophilized PVRV under Zagreb and Essen regimen. A post-marketing parallel control clinical trial was conducted. Totally 240 subjects were assigned to two groups randomly, immunized with lyophilized PVRV under Zagreb and Essen schedule. Solicited adverse events were observed after each dose and unsolicited adverse events were collected. Serum samples were collected on days 0, 7, 14, 42, 180 and 365 to be used to determine immunogenicity level. No severe adverse events (SAE) were observed. The incidence of adverse events under Zagreb and Essen were similar and there was no significant difference between the two groups and within all age groups. Fever and pain were the most frequently reported systemic and local adverse events (AEs) respectively. There were no differences in the GMT and the positive seroconversion rate between these two groups. All participants in the Zagreb group obtained protective effect on day 14, while 99.16% of the subjects obtained in the Essen group. Both groups showed similar enduring immunity. Immunizations under Zagreb and Essen regimens showed similar safety and immunogenicity. For lyophilized PVRV, Zagreb was non-inferior to Essen to patients of all age groups.